2001
DOI: 10.1093/arclin/16.6.587
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance deficits in adults with attention deficit/hyperactivity disorder

Abstract: Neuropsychological deficits in children diagnosed with attention deficit/hyperactivity disorder (ADHD) have been well documented utilizing various neuropsychological tests. Only recently has research begun to examine if similar deficits are present in adults with ADHD. A neuropsychological testing battery was constructed that assessed verbal learning and memory, psychomotor speed, and sustained attention--all demonstrated to be deficient in individuals with ADHD. Fifty-six self-referred nonmedicated adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(30 citation statements)
references
References 0 publications
3
25
0
1
Order By: Relevance
“…Besides the impaired performance on tests of attention and inhibition, executive functions seem to be the most severely impaired cognitive domain in adult ADHD patients, affecting planning, self-monitoring, working memory, fl exibility and set shifting, among others (Torralva et al, 2012b). The dysexecutive profi le of ADHD patients is qualitatively, though not always quantitatively, similar to the pattern observed in adults with frontal lobe damage (Johnson et al, 2001;Shue & Douglas, 1992). Recently, neural correlates of social cognition impairments frequently observed in bvFTD (e.g.…”
Section: Attention Defi Cit Hyperactivity Disordermentioning
confidence: 85%
“…Besides the impaired performance on tests of attention and inhibition, executive functions seem to be the most severely impaired cognitive domain in adult ADHD patients, affecting planning, self-monitoring, working memory, fl exibility and set shifting, among others (Torralva et al, 2012b). The dysexecutive profi le of ADHD patients is qualitatively, though not always quantitatively, similar to the pattern observed in adults with frontal lobe damage (Johnson et al, 2001;Shue & Douglas, 1992). Recently, neural correlates of social cognition impairments frequently observed in bvFTD (e.g.…”
Section: Attention Defi Cit Hyperactivity Disordermentioning
confidence: 85%
“…This is supported from a behavioural perspective, as Johnson et al . () tested 56 adult ADHD patients and 38 typical control adult participants, and found that reaction times were significantly longer in the ADHD group. Additionally, Boonstra et al .…”
Section: Introductionmentioning
confidence: 99%
“…25 ' 27 Similar deficits have been reported in self-referred samples of adults with ADHD. 14 ' 17 ' 18 ' 28 ' 29 If these cognitive deficits are present in parents of children with ADHD, they are likely to have a negative impact upon their parenting skills. Few studies have systematically examined these cognitive functions in the parents of children with ADHD.…”
Section: Introductionmentioning
confidence: 99%